ANALISIS PERTUMBUHAN BIBIT TANAMAN SAWI (Brassica juncea L.) PADA BERBAGAI KOMPOSISI MEDIA TUMBUH - Liastyn Dwika Putri; Nora Augustien Kusumaningrum; Pangesti Nugrahani (UPN VETERAN JAWA TIMUR, 2018)
Various use of non-organic material is often applied in vegetable cultivation, it causes health problems for those who consume while the demand for the community will increase the need for vegetables. So it takes effort in the application of organic vegetable planting by utilizing the surrounding organic materials that are not used. Using of organic material also can increase time of harvesting, so more faster. Time of harvesting depends on growth of plants, more fertile of growing media, more faster plants can be harvested. The objectives of this study were: (1) to analyze the growth of mustard seedlings (Brassica juncea L.) (2) to get the best compositions for mustard seedlings. This research was conducted in Experimental Garden of Faculty of Agriculture of National Development University of